2013
DOI: 10.1063/1.4801440
|View full text |Cite
|
Sign up to set email alerts
|

Conformation-resolved UV spectra of Pb(II) complexes: A gas phase study of the sandwich structures [Pb(toluene)2]2+ and [Pb(benzene)2]2+

Abstract: Toxic heavy metals, such as Pb(2+), have become important targets for the development of efficient receptors that are capable of recognizing their presence as environmental and biological pollutants, and an important part of that receptor-metal characterization process is the provision of spectral evidence that identifies the presence of a metal ion. From results reported here on a combined experimental and theoretical study it is shown that, when complexed with aromatic ligands, Pb(2+) is capable of yielding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 51 publications
0
8
1
Order By: Relevance
“…The UV spectra of [Pb(Benzene) 2 ] 2+ complexes have been recorded in the gas phase from ions that have been held and cooled in an ion trap which was then activated successfully with methane molecules at a selected photon energy. Photofragmentation of [Pb(Benzene) 2 ] 2+ complexes yielded Pb + and benzene + contrary to the previous work of Ma et al [18].…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…The UV spectra of [Pb(Benzene) 2 ] 2+ complexes have been recorded in the gas phase from ions that have been held and cooled in an ion trap which was then activated successfully with methane molecules at a selected photon energy. Photofragmentation of [Pb(Benzene) 2 ] 2+ complexes yielded Pb + and benzene + contrary to the previous work of Ma et al [18].…”
Section: Discussioncontrasting
confidence: 94%
“…The two optimised geometries observed on [Pb(Benzene) 2 ] 2+ were the C 2V eclipse ( Figure 6) and C 2 staggered ( Figure 7). The resultant effect was that the rings of the sandwich complexes were not parallel with angle of 180˚, rather bent hemi-directed geometries with centroid-Pb-centroid angle of ~167˚ however, this angle was slightly larger than the 162 0 obtained previously [18]. The Pb-Benzene bonds were typically found to be focused all the way through only part of the coordination sphere for lead dication complexes, suggesting possibility of the calculated bent structures being expression of this effect.…”
Section: Theorymentioning
confidence: 76%
“…In an earlier study of [Pb(C 6 H 6 ) 2 ] 2+ , the only fragment observed as a result of photoexcitation was C 6 H 6 + . 72 The absence of any metal-containing ion signal (e.g., Pb + ) was attributed to the possibility that a large release of kinetic energy to the fragments from Coulomb explosion could result in ions being ejected from the trap. For a heavy metal ion, collisions with the helium buffer gas would not be sufficient to quench the ion's momentum.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The level of spin contamination provides an indication of the degree of unphysical and/or missing states in the calculated spectrum due to the absence of double-excitations, which need to be correctly described for some spin-adapted configurations arising from a d 9 system with a doublet ground state. A measure of spin contamination is provided by the extent to which the calculated <Ŝ 2 > value differs from the value expected from the same operator for a doublet state, which is 0.75. , Assuming that quartet states (<Ŝ 2 > = 3.75) constitute the primary source of contamination in these dications, that is, | Cu ( benzene ) 2 2 + = C D | doublet + C Q | quartet goodbreak calc 2 = 0.75 | C D | 2 + 3.75 | C Q false| 2 …”
Section: Results and Discussionmentioning
confidence: 99%
“…While for most applications such methods are perfectly adequate, being able to provide both qualitative and quantitative insight into the structure, bonding, reactivity, and spectroscopy of systems of experimental interest 1 and often to the level of "chemical accuracy," there are systems for which these "standard" quantum chemical techniques are unsatisfactory. Thus, for example, the B-O approximation fails to correctly account for the occurrence of conical intersections.…”
Section: Introductionmentioning
confidence: 99%